2017
DOI: 10.1186/s13065-017-0289-x
|View full text |Cite
|
Sign up to set email alerts
|

A review of traditional pharmacological uses, phytochemistry, and pharmacological activities of Tribulus terrestris

Abstract: Tribulus terrestris L. (TT) is an annual plant of the family Zygophyllaceae that has been used for generations to energize, vitalize, and improve sexual function and physical performance in men. The fruits and roots of TT have been used as a folk medicine for thousands of years in China, India, Sudan, and Pakistan. Numerous bioactive phytochemicals, such as saponins and flavonoids, have been isolated and identified from TT that are responsible alone or in combination for various pharmacological activities. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
104
0
12

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(120 citation statements)
references
References 61 publications
4
104
0
12
Order By: Relevance
“…All these medicinal plants may inhibit inflammatory mediators and interact with various cytokines, at least under experimental conditions. The mechanism of action of the oral herbal medicines is likely to be broader than that of non-steroidal anti-inflammatory drugs [23][24][25][26][27]. Although their mechanisms of action have not yet been elucidated in full detail, interactions with mediators of inflammation and cartilage destruction provide a rationale for using them to treat OA complaints.…”
Section: Resultsmentioning
confidence: 99%
“…All these medicinal plants may inhibit inflammatory mediators and interact with various cytokines, at least under experimental conditions. The mechanism of action of the oral herbal medicines is likely to be broader than that of non-steroidal anti-inflammatory drugs [23][24][25][26][27]. Although their mechanisms of action have not yet been elucidated in full detail, interactions with mediators of inflammation and cartilage destruction provide a rationale for using them to treat OA complaints.…”
Section: Resultsmentioning
confidence: 99%
“…The secondary metabolites reach the brain tissues via blood brain barrier 47 to work on central nervous system as potential neuroprotectants. Earlier reports showed that herbs containing flavonoids, tannins and phenolic compounds were found to possess antioxidant property and attenuated cell death induced by oxidative stress Schroeter H2000.…”
Section: Resultsmentioning
confidence: 99%
“…We can also say that disciplined continuous interval training with medication therapy and support of said supplementation directly improves the extension of surgical bypass in any arterial segment, regardless of conduction material, other than haemodynamic autologous reverse lateral or ipsilateral venous conduit or synthetic Dacron material on aortic-femo-Vascular Rehabilitation Benefits of Tribulus Terrestris (TT), Taurine and High Dose Alpha Lipoic Acid (ALA) Supplementation with Interval Walking Training Program after Surgical Vascular Bypass Treatment (Pilot Study) 31 ral, iliacal and femoral levels as well as at the level of improving the objectivity of strength and improving the quality of life (Ivanova, Ivanov, Mladenov et al 2016;Zhu, Du, Meng et al, 2017;Rogerson, Riches, Jennings et al, 2007).…”
Section: Vascular Rehabilitation Benefits Of Tribulus Terrestris (Tt)mentioning
confidence: 99%
“…After primary arterial reconstructive bypass surgery and/or endovascular (PTA stent) and/or surgical-conservative therapy of peripheral arterial stenotic occlusive disease for the stimulation of the immune system in clinical medicine, the expression -immune nutrition in the form of supplementation of Tribulus Terrestris (TT) became naturalized. This supplementation therapeutically works individually or in combination with other preparations (amino acids or other anti-oxidant substances) for enhancing the function of the immune system, optimizing the testosterone in the serum (TS), and improving the properties of blood hemodynamic parameters (Sharifi, Darabi, & Akbarloo, 2003;Svartberg, von Muhlen, & Mathiesen, 2006;Tuncer, Yaymaci, Sati et al, 2009;Berkman, Tanriover, Acar et al, 2009;Silva, Silveira, Ronsani et al,2011;Li, Guan, Liu et al, 2013;Olas, Hamed, Oleszek et al, 2015;Ivanova, Ivanov, Mladenov et al, 2016;Zhu, Du, Meng, Dong et al, 2017). In addition to andropause and the result of testosterone deficit in serum (TS) and predominantly increased incidence of weakened general condition of patients, Taurine is one compound that arises as the ultimate stable product of 1/3 of metabolism of amino acids Cysteine and Methionine (Taurine 2-amino ethane sulfonic acid).…”
Section: Introductionmentioning
confidence: 99%